2021
DOI: 10.1016/j.clnesp.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malnutrition and analysis of related factors among adult patients with the Coronavirus Disease 2019 (COVID 19) in a tertiary government hospital: The MalnutriCoV study

Abstract: Background and Aims As of November 2020, the Coronavirus Disease 2019 (COVID 19) has infected more than 396,000 people in the Philippines. Although no study has been done on malnutrition among a general cohort of patients with COVID 19, it has long been associated with increased mortality and poor long-term outcomes. We aimed to determine the prevalence of malnutrition among patients with COVID 19 admitted in a tertiary government hospital. Methods Cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…In viral infections such as COVID-19, the effect of nutrition on catching the disease and/or the prognosis of the disease should not be ignored. In line with our findings, in a study conducted with 355 adults, the prevalence of malnutrition was high (71.83%) in a general cohort of COVID-19 patients [ 14 ]. In addition, Allard et al reported that about 40% of patients admitted for COVID-19 pneumonia had malnutrition and about 35% of them had severe nutritional risk [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In viral infections such as COVID-19, the effect of nutrition on catching the disease and/or the prognosis of the disease should not be ignored. In line with our findings, in a study conducted with 355 adults, the prevalence of malnutrition was high (71.83%) in a general cohort of COVID-19 patients [ 14 ]. In addition, Allard et al reported that about 40% of patients admitted for COVID-19 pneumonia had malnutrition and about 35% of them had severe nutritional risk [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in the recently defined COVID-19, malnutrition accelerates the inflammatory process and is associated with a long hospitalization period [ 2 , 12 , 13 ]. Therefore, it is very important to evaluate hospitalized patients in terms of malnutrition risk and take necessary precautions as well as monitor nutrition status during the clinical course of the disease [ 13 , 14 ]. The nutrition status of patients with COVID-19 should be taken into consideration, and most of all, it should be remembered that malnutrition can be a prognostic factor for morbidity and mortality related to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be imperative to establish malnutrition screening practices in post-COVID 19 patients who have recovered from acute infection. 6,7 The strengths of our study include the largest cohort of patients with follow-up data of COVID-19-associated GI symptoms to date; a diverse patient population across multiple hospitals in Long Island, Manhattan, Queens, and Staten Island making results more generalizable; and manual chart review to confirm GI findings on admission and follow-up visits. Moreover, patients were diagnosed with malnutrition by a dedicated nutrition service.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with malnutrition include older age, severity of pneumonia, and chronic kidney disease. However, there was no data on the clinical outcomes of the patients [6].…”
Section: Introductionmentioning
confidence: 99%